PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI CANVA UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS V SD - Is Oktaria Pratiwi; Riski Alwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Technology is very important to achieve learning goals today. However, the quality of learning in the field is still very low, and students feel bored with classroom learning. The purpose of this study is to develop learning media that can increase student interest. Research and Depelovement is the method used. The data collection method is using interviews, observations, questionnaires, and documentation. The instruments used are product validation sheets and teacher and student response sheets. In this study, the value of media experts was 84.6%, material experts 81.67%. In addition, the teacher's response showed a percentage of 84.51% and students 83.36%. The results showed that Canva-based video learning media met the validity criteria evaluated by material experts and media experts. In addition, based on the trial use of the media in learning, students show high interest in learning. The results of the questionnaire given to students show that students are more interested in learning than before. This study found that video learning media used through Canva application can increase students' interest in learning.